The Glycyrrhiza glabra L. crude extract alleviates lipid accumulation in NAFLD by activating Nrf2 and promoting autophagy - Yunfei Wei; Meiyu Jin; Hao Yu; Xiaoning Hou; Lilei Zhao; Lu Ding; Jiaqi Cheng; Jiazhang Qiu; Haihua Feng (Journal of Functional Foods, 2024)
Glycyrrhiza glabra L. is a common heritage herbal medicine rich in antioxidant compounds such as flavonoids and triterpenoids. Non-alcoholic fatty liver disease has been the global prevalent chronic liver disorder. To investigate the curative role and mechanism of the Glycyrrhiza glabra L. crude extract on NAFLD, in vitro, we used oleic acid, palmitic acid, ML-385 and 3-MA to stimulate HepG2 cells. In vivo, we used Tyloxapol to inject mice intraperitoneally to establish an acute model, and high-fat diet to feed wild-type, Nrf2-/- and ATG5flox/flox mice to establish a chronic model. We used high performance liquid chromatography to analyse the content of major bioactive components in the Glycyrrhiza glabra L. crude extract. Our study found the Glycyrrhiza glabra L. crude extract could effectively alleviate lipid accumulation in non-alcoholic fatty liver disease, activate Nrf2 and promote autophagy. However, this alleviating effect disappeared when the Nrf2 and autophagy were inhibited separately. Our study demonstrates that crude extraction of active ingredients from traditional herbal medicines may be a potentially inexpensive, rapid and safe approach to alleviate lipid accumulation in non-alcoholic fatty liver disease.